Less is more! Uluzzian technical behaviour at the cave site of Castelcivita (southern Italy). (August 2022) - Rossini, Matteo; Marciani, Giulia; Arrighi, Simona; Pereira Santos, Marcos César; Spagnolo, Vincenzo; Ronchitelli, Annamaria; Benazzi, Stefano; Moroni, Adriana
Highlights: Technological analysis of the Uluzzian lithic assemblage of Castelcivita. Focus on the cores' mode of exploitation employed by early Homo sapiens in Italy. The production is characterised by the research of small flakes and blades/bladelets. Bipolar technique on anvil is a distinctive feature of the Uluzzian technocomplex. Uluzzian production model is characterised by the idea of "less is more". Abstract: The Uluzzian techno-complex is one of the first evidence for Homo sapiens successful dispersal in Europe. It develops from about 45 to 40 ka cal. BP, i.e., during the so-called "transition" from Middle to Upper Palaeolithic, the period in which Neandertals went extinct. The cave site of Castelcivita (southern Italy) contains a well-preserved stratigraphic sequence concentrated in this specific phase as it comprises Late-Final Mousterian, Uluzzian and Protoaurignacian layers. Here we present the technological study of the Uluzzian lithic assemblage found in layer rpi of this site. The study specifically focuses on the methods used to exploit cores, characterised by a low degree of technical investment in which management of the convexities and angles of debitage are almost absent. The most used percussion technique is bipolar striking on anvil. Despite they are not standardized, the obtained products show features which make them apt to be used in composite devices. The use of local raw materials, the production of small items and the marginal role of retouched pieces, among which some lunates are present, are also typical of the rpi assemblage. Based on these results we argue that the strengths of the Castelcivita rpi technological approach are its versatility, and the reduction of unnecessary costs related to raw material procurement, the configuration of the core and the management of the convexities. All these elements tend to the use of the available resources in the most productive way, without the final product losing efficiency, according to the concept "less is more". A hypothesis possibly explaining this technical behaviour is provided in the conclusions.